Участие польских военных чинов в боевых действиях на Север- ном Кавказе в 30-х гг. XIX в. (на примере Тенгинского полка) - Клычников, Юрий (Acta Polono-Ruthenica, 2021)
Among the servicemen of the Separate Caucasian Corps, there were also immigrants from Poland. The circumstances of their appearance in the region were different. The captured soldiers and officers of the liquidated army of the Kingdom of Poland, as well as persons distributed according to conscription lists, etc., were sent here. They were sent to different units, but a lot of them were assigned to the Tengin Regiment, which was considered the most suitable for reforming the “unreliable ones”. The regiment took an active part in hostilities and was involved in the construction of a chain of fortifications on the Black Sea coast of the Caucasus. For this, the participants in the battles, including the Poles, were decorated by the command and personally by the emperor.